Basic Needs, Wellbeing and Morality Fulfilling Human Potential (Springer International Publishing, 2018)
'In this fascinating book, the three authors employ a contemporary neurobiological framework that extends the insights of legendary psychologist Abraham Maslow regarding the importance of fulfilling basic needs. The authors convincingly show that wellbeing in early life orients a child to compassionate behavior instead of self-centered protectionism. The research described in this book adds significantly to our knowledge about the effects of parenting on children's basic needs and on their subsequent socio-moral development.' -Dr. William Damon, Professor at the Stanford Graduate School of Education and Director of the Stanford Center on Adolescence, USA Basic needs fulfilment is fundamental to becoming human and reaching one's potential. Extending the BUCET list proposed by Susan Fiske - which includes belonging, understanding, control/competence, autonomy, self-enhancement, trust, purpose and life satisfaction - this book demonstrates that the fulfilment of basic needs predicts adult physical and mental health, as well as sociality and morality. The authors suggest that meeting basic needs in childhood vitally shapes one's trajectory for self-actualization, and that initiatives aimed at human wellbeing should include a greater emphasis on early childhood experience. Through contemporaneous and retrospective research in childhood, the authors argue that basic need-fulfilment is key to the development of the self and the possibility of reaching one's full potential. This book will be of interest to scholars of human wellbeing and societal flourishing, as well as to health workers and educators. Darcia Narvaez is Professor of Psychology at the University of Notre Dame, USA. Her research interests are focused around moral development and flourishing across the lifespan.